Online mediation in Malaysia: with reference to the practice of mediation in the Family Support Division of the Syariah Judiciary Department - Abdul Hak, Nora (Onikilevha Yayincilika.s Istanbul Turkey, 2019)
Mediation as one of alternative dispute resolution(ADR) mechanisms is getting popular and becoming a prefered choice amongst the disputing parties. Mediation process is more relax, inexpensive and has many advantages. Online mediation is a new development in mediation practice in many countries now. However, Malaysia has yet to fully practice online mediation in resolving the dispute. In this digitalization era, it is important for Malaysia to have an online mediation since many Malaysian citizens are working overseas either as a professional or non-professional. The existence of online mediation system will assist the parties if there is a need to attend mediation session in Malaysia. It will further support the current mediation centres in Malaysia to expand their coverage globally. In future, there is a need to introduce specific law to regulate the practice of online mediation. Currently, the Family Support Division of the Syariah Judiciary Department offers online mediation to their clients. The division has just launched its latest guidelines book on mediation which covers online mediation as well. The paper adopts library based and qualitative research method. The aim of the paper is to discuss the advantages and disadvantages of online mediation, the issues faced by parties and the challenges of online mediation in Malaysia. Subsequently, in this paper, the roles and functions of the Family Support Division in helping single mothers and their children are discussed and it also proposes the procedures to be adopted by the Division that provides online mediation service to their cllients.